1987
DOI: 10.3109/02713688709044503
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide in the Rabbit Anterior Chamber: Effects on Glutathione, and Catalase Effects on Peroxide Kinetics

Abstract: Intracameral hydrogen peroxide (H2O2) is cleared at a faster rate in young (t1/2, 93 seconds) than in adult (t1/2, 109 seconds) rabbits. Extrapolated zero time concentrations of H2O2 were 3.3 mM in adults and 3.2 mM in young. The more rapid disappearance of H2O2 correlated with greater catalase levels in iris (35%) and corneal endothelium (50%) in young as compared to adult animals. Catalase levels have been found to be reduced in ocular tissues with 3-amino-1H-1,2,4-triazole (3AT) in a dose-related manner up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Enzymes were determined as follows: glutathione reductase was assayed as de scribed by Lopez-Barea and Lee [20]; glutathione was assayed by the method of Tietze [21] as described by Csukas et al [12], Riley et al [22], and Riley [23]. Glutathione assays were performed in Rochester after tissues were extracted from the eye, weighed, and placed in 0.2 ml of 5 mA/ ethylenediaminetetraacetic acid.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Enzymes were determined as follows: glutathione reductase was assayed as de scribed by Lopez-Barea and Lee [20]; glutathione was assayed by the method of Tietze [21] as described by Csukas et al [12], Riley et al [22], and Riley [23]. Glutathione assays were performed in Rochester after tissues were extracted from the eye, weighed, and placed in 0.2 ml of 5 mA/ ethylenediaminetetraacetic acid.…”
Section: Methodsmentioning
confidence: 99%
“…The tissues surrounding the anterior cham ber contain both catalase and the constitu ents of the glutathione-redox system [11], and both systems are capable of detoxifying H2O2. Reduction of catalase activity with 3-aminotriazole (3AT) caused a young eye, which normally had little response to and recovered rapidly from an intracameral in jection of H2O2, to show a pathological re sponse to exogenous intracameral H20 2 [12,13], Eyes of normal adult rabbits also show a strong pathological reaction to intracameral H2O2, and 3AT pretreatment exacerbated this response. The difference between the reaction of young and adult eyes to intracameral H2O2 in part reflects the demonstrated loss of tissue catalase activity with increasing age [12,14], The studies cited above [12,13] using intracameral H20 2 injection into the ante rior chamber utilized quantities of H2O2 such that the final aqueous humor concen tration was about 3 mM, both by calculation and extrapolation of the decay curve of H20 2 to zero time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure effectively eliminates tis sue blood contamination (as determined by tissue hemoglobin content) while not producing tissue swell ing (as indicated by the constancy of tissue mg wet weight/mg protein; 20.64 ± 2.99 for perfused control animals vs. 22.55 ± 2.02 for nonperfused control ani mals, p > 0.60). Irides were excised, weighed, placed in 2 ml phosphate buffer (tissue concentration ap proximately 20 mg/ml buffer) pH 7.4 at 4 °C, homog enized for 15 s, sonicated for 15s and then centri fuged at 12,000 g for 5 min [17].…”
Section: Methodsmentioning
confidence: 99%
“…However, some studies have been able to demonstrate the presence of H20 2 in the human and animal aqueous and cataractous hu man lenses, using Mapsoms technique meant primarily for qualitative H20 2 detection. This is based on the peroxidase-driven oxidation of leukodichlorophenol-indophenol by H20 2 with consequent generation of blue color and spectrophotometric measurement of the latter [5][6][7][8][9], The presence of H20 2 in the lens and aque ous humor of several animal species, and in the aqueous humor of cataract patients, has also been demonstrated using a radioisotopic meth od based on the peroxide-dependent decarbox ylation of l-M C-(i-ketoacids and measuring radioisotopically the UC 0 2 produced [10,11]. The rat lens peroxide level in the latter studies were found to be of the order of 10 4 M .…”
Section: Introductionmentioning
confidence: 99%